Analisis Uji Balistik Komposit Serat Pelepah Salak Dengan Resin Epoksi dan Silicon Carbida (SiC) Menggunakan Metode Vacuum Bag - Rivaldy Armando Kamal; Muhammad Abdul Ghofur (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2021)
Composites are two or more kinds of materials that are combined or combined on a macroscopic scale (can be seen directly by the eye) so that they become new, more useful materials. So far, the use of composites uses materials made of metal or steel. This research was carried out to make a natural fiber reinforced composite material, namely salak midrib which can be used as a substitute for metal materials used in Indonesian Air Force defense equipment such as bullet-proof vests. This study aims to determine the mechanical properties in the form of tensile strength and hardness values ​​of salak fiber composites and to determine the ballistic strength of a composite fired with 9 mm caliber bullets (MU-1TJ) with several variations of firing distance according to NIJ standards using Precision Shooting Test Equipment. The manufacture of this composite uses the Vacuum Bag composite method. From the test results, the mechanical properties of the salak midrib fiber composite are in the form of a tensile strength of 21.46 N/mm2 and a hardness value of 23.64 HV. The results of the ballistic test were 2 specimens that met the NIJ standard and 2 specimens that did not meet the NIJ standard. The first specimen that meets the NIJ level IIA standard is a composite specimen with the composition of Kevlar and SiC Filler, where the results from a shooting distance of 30 mm have a BFS of 6.26 mm, a distance of 25 m has a BFS of 11.86 mm, a distance of 10 m and 5 m bullets penetrate the specimen. . The second specimen that meets NIJ level II and IIA standards is a hybrid composite specimen with a composition of blended bark fiber, kevlar fiber, SiC and Al7075-T6 fillers, where the results of firing at a distance of 30 mm have a BFS of 0 mm, a distance of 25 m has a BFS of 0 mm, a distance of 10 m has a BFS of 0 mm and a distance of 5 m has a BFS of 0 mm (all bullets did not penetrate the specimen).